Adição de água em rações para suínos em crescimento e terminação - FARIAS, Leonardo Atta (2010)
In this research, three experiments were conducted. The first and the second ones were conducted to evaluate the effects of adding water to mash rations on nutrient digestibility, energy performance, water intake and excrement quality of pigs at the growing and finishing phases(the evaluation of carcass traits was performed), respectively. Finally, a last experiment was carried out to evaluate the proliferation of fungi in the diets of finishing pigs with different levels of water addition and at different storage times. The variables analyzed in the first two experiments were nutrients and energy digestibility and metabolism, nitrogen balance, moisture rate, fecal nitrogen and phosphorus, and performance variables. For the second trial, the carcass traits were also evaluated after slaughtering. In the third experiment, the number of fungal colony-forming units in the diets was evaluated with and without the use of antifungal and at different storage times. The addition of water to pig diets at growing-finishing phases does not influence the apparent nutrient digestibility, or the performance of the animals when they are fed twice a day. There is a reduction of fresh water intake, and of phosphorus excretion. Carcass composition was not affected. The addition of water to the diets of pigs in the finishing phase increases the production of fungi over storage time.